Soluções para um problema parabólico com uma fonte não linear localizada - Coelho Junior, João Batista (2017)
In this paper, we discussed the article ”The Semilinear Heat Equation with a Localized Nonlinear Source and Non-Continuous Initial Data”due to Lucas Ferreira and Elder Villamizar-Roa. In this paper they consider the Cauchy problem for the Semilinear Heat Equation with a nonlinear term presenting a nonlinear source centered on a closed region of a spatial domain. Under these conditions, they prove that this problem admits local solution and that this solution depends continuously on the initial data and is positive.